Conceptual Design of Hybrid Aerial Vehicle for Venus Exploration - Jesus Rosales; Addison Miller; Edgar Nunez; Andreas Gross; Nancy Chanover (Aerospace, 2023)
The conceptual design of a hybrid aerial vehicle for the exploration of the upper Venus atmosphere is presented. The vehicle will float like a balloon and harvest solar energy which is stored in batteries. The neutral buoyancy reduces the energy consumption and makes the vehicle robust and durable. Energy stored in the batteries can be used for powered flight with good horizontal and vertical mobility to explore aspects of the atmosphere. The vehicle is intended to operate near 55.3 km altitude and to explore the cloud layer of the planet. The vehicle takes its inspiration from the Stingray inflatable wing by Prospective Concepts. Based on a trade study, the wing span was set to 25 m. Equations are developed for the altitude, gas and skin temperature, and skin stress during neutrally buoyant flight. To keep the equations in a simplified analytical form, the complex compartmentalized gas pockets of the vehicle are lumped into a single gas sphere. The equations take into account the volumetric expansion of the structure and the requirement that the differential pressure needs to be large enough to allow for brief periods of powered flight without significant structural deformation. An aerodynamic analysis provides the lift and drag coefficient curves and indicates that the vehicle is pitch-stable. A powered flight analysis shows that an airspeed of 30 m/s can be maintained for 31 min at 55 km and 69 min at 69 km altitude.